"Mayhem! Absolute Mayhem!" Exploring the promotional metadiscursive features in the sportscasts of the 2014 FIFA World Cup semifinal between Brazil and Germany. (December 2016) - Saidian, Soheil; Jalilifar, Alireza
Abstract: With an accumulated number of over 190 min of the Persian and English sportscasts of the 2014 FIFA World Cup semifinal between Brazil and Germany analyzed, this study focused on the promotional metadiscursive features used by the commentators while reporting this game in their respective languages. The transcribed sportscasts were first examined in order to reveal the different constituents modified by existing promotional elements and to discover the functions they fulfilled in the context. A careful analysis of the data yielded 8 different general categories that were modified by promotional components, namely players, coaches and their staff and referees comprising the first group, accompanied by spectators, competitions, institutions, the media, venues, the weather and miscellaneous features constituting the other seven categories. The functions observed in the reports were illocution markers, attitude markers and commentary. The study provides evidence that promotional metadiscursive features are an integral part of soccer sportscasts, and it can also be considered as a platform on which to further develop similar research prospects in less appreciated areas of inquiry. Highlights: The items described by the promotional features are placed in 8 categories. The reporter uses various traits to meet distinct functions in making assertions. The functions identified in the reports are similar in both languages.